GSDMD membrane pore is critical for IL-1β release and antagonizing IL-1β by hepatocyte-specific nanobiologics is a promising therapeutics for murine alcoholic steatohepatitis. (January 2020) - Luan, Jingyun; Chen, Wei; Fan, Jiajun; Wang, Shaofei; Zhang, Xuyao; Zai, Wenjing; Jin, Xin; Wang, Yichen; Feng, Zhenyi; Zhang, Jinghui; Liu, Ming-Lin; Ju, Dianwen
Abstract: Excessive release of interleukin-1β (IL-1β) is well-known to provoke cascades of inflammatory responses thus contributing to the pathogenesis of alcohol-induced steatohepatitis (ASH), but the cellular mechanism that regulates IL-1β release during ASH remains unclear. Herein, we identified that gasdermin D (GSDMD) membrane pore is critical in mediating IL-1β hypersecretion from chronic ethanol or acetaldehyde-stimulated macrophages. Deletion of GSDMD reduced IL-1β release and ameliorated alcoholic steatohepatitis in vivo . These findings uncovered a novel mechanism regarding the IL-1β release in ASH, and also indicated the therapeutic potential of IL-1β blockade. Interleukin-1 receptor antagonist (IL-1Ra) is protective to ASH by blocking IL-1β, but it has a short biological half-life (4–6 h) and lower liver concentrations. Thus, we constructed a therapeutic plasmid pVAX1-IL-1Ra-ApoAI (pVAX1-IA) encoding IL-1Ra anchored to the liver-targeting protein apolipoprotein A-I (ApoAI), and developed hepatocyte-specific nanobiologics (Glipo-pVAX1-IA) by galactose functionalization for local and prolonged expression of IL-1Ra in liver. Data presented here showed that Glipo-pVAX1-IA facilitated efficient uptake of gene cargos by hepatocytes. The biodistribution studies confirmed a predominant hepatocytes internalization, but a minimal kupffer cells uptake of Glipo-pVAX1-IA following intravenous injection. The locally secreted IL-1Ra attenuated alcohol-induced steatohepatisis and infiltration of inflammatory cells. Together, our results unraveled the critical role of GSDMD membrane pore in IL-1β hypersecretion and highlighted the hepatocyte-specific Glipo-pVAX1-IA nanobiologics as a promising therapeutic strategy for ASH. Graphical abstract: Excessive ethanol feeding contributes to the cleavage of caspase-1, which processes the maturation of IL-1β and cleaves inactive GSDMD into active GSDMD-N. GSDMD-N forms pores on the plasma membrane that mediates IL-1β secretion into the cytoplasm. Once released, IL-1β binds to IL-1R1 and IL-1RAcP to induce the hepatocyte damage, as well as infiltrates Th17 cells and neutrophils into the damaged regions, leading to aggravated liver steatosis and inflammation. Here, we developed the hepatocyte-targeted delivery strategy by packaging pVAX1-IA into galactose-functioned nanobiologics. The resulting Glipo-pVAX1-IA was specifically internalized into hepatocytes by ASGPR-mediated endocytosis and delivered into nucleus for transcription. The fusion protein IL-1Ra-ApoAI was expressed that promotes secondary targeting to hepatocytes by ApoAI-mediated binding with SR-BI receptor, which contributed to the competitive binding of IL-1R1 by IL-1Ra, thus blocking the pathogenic effects of IL-1β and attenuating ASH. Image 1